Waste management in schools as part of sustainable development - Haniva, Respita; Butar Butar, Senita; Ambarita, Nita (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Waste management in schools plays a crucial role in promoting sustainable development, as education serves as a precursor to raising awareness and instilling habits in society. This research seeks to understand the existing body of knowledge on waste management in schools, with a particular focus on primary to junior high school levels, as a facet of sustainable development over the period 2010 to 2023. The research uses bibliometric analysis through tools such as VOSviewer and Publish or Perish. The research yielded a total of 63 published articles. The main findings include: (1) the most publications on waste management in schools occurred in 2022, but the most influential year was 2021; (2) the number of publications, institutions, journal rankings, and countries that produced research in this field; (3) research collaboration was not significant; (4) the most prominent journals in this field were Recycling and Science of the Total Environment; and (5) the common themes of articles in this field include waste management in schools, waste impacts, waste management system evaluation, sustainable development, and environmental management. These results will greatly assist readers in identifying research priorities related to school waste management and sustainable development. The recognition of collaborative efforts between different countries will bring new issues to the forefront of school waste management research and encourage collaboration between nations. Practically, this study provides a comprehensive review of the literature on school waste management as an integral part of sustainable development.